The Relationship Between A History Of Anemia During Pregnancy And The Incidence Of Stunting In Sumbermulyo Village, Jogoroto, Jombang - Nur Panca Aprillia; Siswati Siswati (CV. AFDIFAL MAJU BERKAH, 2026)
Stunting is a persistent dietary problem that affects physical growth and cognitive development in children. One significant risk factor is anemia during pregnancy. In Sumbermulyo Village, a high prevalence of stunting was recorded, with many mothers having a history of anemia in pregnancy. This research seeks to examine the correlation between pregnancy history anemia (second trimester) and the incidence of stunting in toddlers in Sumbermulyo Village, Jogoroto, Jombang. This quantitative study uses a correlational design with a retrospective approach. The study population consists of 30 mothers with stunted toddlers, selected using a total sampling method. Secondary data were obtained from maternal hemoglobin (Hb) history records and toddler height measurements. Data analysis was conducted with the Spearman Rank statistical test. The findings of this research indicate that a majority of mothers (63.3%) had anemia during the second trimester. The correlation test findings indicate a significant value of p = 0.011 (p < 0.05) and a correlation coefficient of -0.459. This signifies a substantial association of moderate intensity and negative correlation between a history of anemia during pregnancy and the incidence of stunting. It may be argued that decreased maternal hemoglobin levels during pregnancy correlate with an elevated risk of childhood stunting. Interventions to prevent anemia in pregnant women are essential as a main approach to reduce stunting rates.